Pengenalan Sistem Tanam Hidroponik di MTs YPM 5 Desa Gedangan Jombang - Mohamad Nasirudin; Fitri Umardiyah; Tiara Cahyani; Baita Fitrianah; Aulia Saharani; Ibrahim Yusuf Al Farros; Niswah Qonita; Salim Ashar; Wisnu Siwi Satiti; Khusnul Khotimah (Jumat Pendidikan: Jurnal Pengabdian Masyarakat, 2026)
This community engagement program was carried out at MTs YPM 5 Gedangan with the focus on providing education and practical training in hydroponic plant cultivation. The issue identified in the school community was the lack of knowledge and skills among students regarding environmentally friendly agricultural practices and alternative cultivation methods that can be applied in limited land areas. The main objective of the program was to improve the awareness and competence of students in understanding hydroponic techniques as a form of practical science learning that supports food security and environmental sustainability. The approach used was participatory learning through direct practice, mentoring, and demonstrations conducted in collaboration with teachers and students. The strategy involved the introduction of hydroponic concepts, the preparation of simple cultivation tools, and hands-on planting activities that engaged students in every stage of the process. The results of the program showed that students gained better knowledge of hydroponic cultivation, developed practical skills in preparing and maintaining plants, and demonstrated increased interest in applying sustainable agricultural practices. In addition, the activity encouraged collaborative learning, built student creativity, and provided a model for integrating practical science-based projects into the school curriculum. Overall, the program created positive outcomes by equipping students with new competencies while strengthening school efforts to promote environmental awareness and sustainable education.